Opposite Effects of Mineral Dust Nonsphericity and Size on Dust‐Induced Snow Albedo Reduction - Tenglong Shi; Cenlin He; Daizhou Zhang; Xuelei Zhang; Xiaoying Niu; Yuxuan Xing; Yang Chen; Jiecan Cui; Wei Pu; Xin Wang (Geophysical Research Letters)
Abstract We quantified the combined effects of mineral dust nonsphericity and size on snow albedo reduction using the MOPSMAP (Modeled optical properties of ensembles of aerosol particles) package and SAMDS (Spectral Albedo Model for Dirty Snow) with the consideration of dust from Sahara, Greenland, San Juan Mountains, and Tibetan Plateau. Results indicate that the dust‐induced albedo reduction decreases by up to 30% as the effective radii of dust particles increase in 1–5 μm. Nonspherical dust enhances snow albedo reduction relative to spherical dust by up to 20%. Stronger enhancements are obtained for higher dust concentration and larger dust size. Furthermore, the dust nonsphericity‐induced enhancement of snow albedo reduction is more pronounced for more‐absorptive dust. Finally, we develop a new parameterization for quantifying the dependence of snow albedo reduction on dust nonsphericity and size, and provide a convenient way for assessing the climate impacts of dust in snow.